The Relationship Between Stress and Anxiety with the Occurrence of Functional Dyspepsia among Medical Students of Sumatera Utara University - Aries, Tri Mulyani; Rey, Imelda (The Indonesian Society for Digestive Endoscopy, 2024)
Background: Functional dyspepsia is characterized by upper gastrointestinal symptoms like epigastric bloating, pain, and early satiation without structural disease evidence, including negative findings on endoscopy. Psychological triggers, such as stress and anxiety, may influence its occurrence. Previous research in Indonesia, including studies at Tarumanegara University, Mulawarman University, and the Islamic University of North Sumatra, has found associations between psychological factors and functional dyspepsia symptoms. Most respondents experienced dyspepsia linked to stress and anxiety. A study on patients at Dr. M. Jamil Hospital also confirmed this relationship. Building on the data mentioned, this study aims to explore and confirm the relationship between stress, anxiety, and the occurrence of functional dyspepsia in medical students at Sumatera Utara University.Methods: This research utilized a cross-sectional analytical approach with a sample of 261 medical students from Sumatera Utara University, selected via quota sampling, and applied the Rome IV and DASS-21 criteria questionnaires. Data were collected from September 2022 until October 2022. Results: This study showed a 47.9% prevalence of functional dyspepsia among respondents, with 44.1% experiencing moderate stress and 72.4% having very severe anxiety. The Chi-square test revealed significant relationships between stress (p=0.026) and anxiety (p=0.038) with functional dyspepsia incidence. Spearman correlation tests further confirmed significant relationships between stress levels (p=0.049) and anxiety levels (p=0.030) and functional dyspepsia. Conclusion: There is a relationship between stress and anxiety with the incidence of functional dyspepsia in medical students of Sumatera Utara University.